2021
DOI: 10.3390/plants10081648
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Anti-Photoaging Effects on UVA-Irradiated Human Fibroblasts of Rosmarinic Acid Enriched Extract Prepared from Thunbergia laurifolia Leaves

Abstract: The current study investigated the inhibiting effect on reactive oxygen species (ROS), reactive nitrogen species (RNS), and matrix metalloproteinase-1 (MMP-1) production in a cell-based study of standardized rosmarinic acid enriched extract (SRAEE) prepared from Thunbergia laurifolia leaves. HPLC chromatogram revealed that rosmarinic acid is a major component in prepared SRAEE, followed by caffeic acid. SRAEE exhibited antioxidant activity both in vitro and cell-based studies. SRAEE showed scavenging effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Antioxidant compounds have been shown to have the ability to inhibit the emergence and scavenge of free radicals in a variety of ways [ 1 ]. For example, they block oxidative enzymes, upregulate antioxidant enzymes, and directly respond to free radicals to minimize oxidative damage [ 2 , 3 , 4 ]. Thus, measuring total antioxidant capacity (TAC) is an important indicator expressed with various methods, especially the scavenging activity of free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH • ) and total phenolic content (TPC) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant compounds have been shown to have the ability to inhibit the emergence and scavenge of free radicals in a variety of ways [ 1 ]. For example, they block oxidative enzymes, upregulate antioxidant enzymes, and directly respond to free radicals to minimize oxidative damage [ 2 , 3 , 4 ]. Thus, measuring total antioxidant capacity (TAC) is an important indicator expressed with various methods, especially the scavenging activity of free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH • ) and total phenolic content (TPC) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…RA prevents ultraviolet rays-induced photodamage (Gupta et al 2021 ; Huerta-Madroñal et al 2021 ). Pattananandecha et al ( 2021 ) reported anti-oxidant activity and anti-photoaging effects of RA extracts on UVA-mediated damage on human fibroblast from the Thunbergia laurifolia plant. Figure 1 demonstrates RA's anti-inflammatory, anti-oxidant, anti-microbial, anti-diabetic, anti-cancer, and anti-hypertensive potential (Bulgakov et al 2012 ; Zhang et al 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin glucoside and quercetin rhamnoside, which are other chemical components of MCB, showed antioxidant effects [ 20 ]. Rosmarinic acid inhibited the production of reactive oxygen species (ROS) in human fibroblast cells induced by ultraviolet A radiation (UVA) [ 21 ]. In the liver, isoquercetin promoted the phosphorylation of acetyl-CoA carboxylase and increased the expression of PPARα and farnesoid X receptor.…”
Section: Introductionmentioning
confidence: 99%